The Degree of Availability of Knowledge Economy Skills among Postgraduates in the Faculty of Education at the Islamic University - Palestine - Manal N. Qwaider; Amal Nabil Qeshta (University of Science and Technology, Yemen, 2021)
This study aimed at identifying the extent to which knowledge economy skills are available among postgraduates in the Faculty of Education at the Islamic University in Gaza. The researchers used the analytical descriptive method. The study population consisted of (367) postgraduates in (2018-2019), and the study sample consisted of (195) postgraduates selected by the simple random method. Then data were analyzed by (SPSS). The results showed that knowledge economy skills were available among postgraduates at a high degree and relative weight of %79.20. Moreover, there were no statistically significant differences between the study participants due to the variables of major, cumulative average and gender, except for the dimensions of creativity and innovation skills and critical thinking skills, in favor of males. The study recommended that there should be more focus on creative and critical thinking; and postgraduate students should receive more training on  self-learning and decision-making skills, and should be encouraged for more participation, research and experiment. Keywords: knowledge economy skills, postgraduates, Islamic University.